Using Real-Time Electron Microscopy To Explore the Effects of Transition-Metal Composition on the Local Thermal Stability in Charged Li(x)Nli(y)Mn(z)Co(1-y-z)O(2) Cathode Materials - Hwang, Sooyeon; Kim, Seung Min; Bak, Seong-Min; Kim, Se Young; Cho, Byung-Won; Chung, Kyung Yoon; Lee, Jeong Yong; Stach, Eric A.; Chang, Wonyoung (AMER CHEMICAL SOC, 2015)
In this work, we use in situ transmission electron microscopy (TEM) to investigate the thermal decomposition that occurs at the surface of charged LixNiyMnzCo1-y-zO2 (NMC) cathode materials of different composition (with y, z = 0.8, 0.1, and 0.6, 0.2, and 0.4,and 0.3), after they have been charged to their practical upper limit voltage (4.3 V). By heating these materials inside the TEM, we are able to directly characterize near surface changes in both their electronic structure (using electron energy loss spectroscopy) and crystal structure and morphology (using electron diffraction and bright-field imaging). The most Ni-rich material (y, z = 0.8, 0.1) is found to be thermally unstable at significantly lower temperatures than the other compositionsthis is manifested by changes in both the electronic structure and the onset of phase transitions at temperatures as low as 100 degrees C. Electron energy loss spectroscopy indicates that (i) the thermally induced reduction of Ni ions drives these changes, and (ii) this is exacerbated by the presence of an additional redox reaction that occurs at 4.2 V in the y, z = 0.8, 0.1 material. Exploration of individual particles shows that there are substantial variations in the onset temperatures and overall extent of these changes. Of the compositions studied, the composition of y, z = 0.6, 0.2 has the optimal combination of high energy density and reasonable thermal stability. The observations herein demonstrate that real-time electron microscopy provide direct insight into the changes that occur in cathode materials with temperature, allowing optimization of different alloy concentrations to maximize overall performance.
Keywords: STRUCTURAL-CHANGES; RESOLVED XRD; DECOMPOSITION; COMPENSATION; EVOLUTION